Constraints on coccolithophores under ocean acidification obtained from boron and carbon geochemical approaches. (15th December 2021) - Liu, Yi-Wei; Rokitta, Sebastian D; Rost, Björn; Eagle, Robert A.
Abstract: Ocean acidification (OA) appears to have diverse impacts on calcareous coccolithophores, but the cellular processes underlying these responses are not well understood. Here we use stable boron and carbon isotopes, B/Ca ratios, as well as inorganic and organic carbon production rates to investigate the carbon utilization and the internal pH regulation at the site of calcification in Emiliania huxleyi, Calcidiscus leptoporus and Pleurochrysis carterae cultured over a wide p CO2 range (180–1000 μatm). Despite large variability, the geochemistry data indicate species-specific modes of pH control and differences in the utilization of inorganic carbon. Boron isotope data suggest that all three species generally upregulate the pH of the calcification fluid (pHCF ) compared to surrounding seawater, which coincides with relatively constant growth rates and cellular ratios of inorganic to organic carbon. Furthermore, species exhibit different strategies in regulating their pHCF, i.e., two species maintain homeostasis (pHCF = ∼8.7), while one species shows a constant offset to the surrounding seawater (ΔpH = ∼0.6 units) over the entire tested p CO2 range. In addition to these different strategies, carbon isotope data suggests that high plasticity in the utilization of dissolved inorganic carbon might be an explanation for species-specific differences in coccolithophore responses to OA.